Kallikreins as Biomarkers for Prostate Cancer. (7th April 2014) - Hong, Sung Kyu
Abstract : The introduction of testing for prostate-specific antigen (PSA), a member of the fifteen-gene family of kallikrein-related peptidases and also known as kallikrein-related peptidase 3 ( KLK3 ), in blood has revolutionized both the detection and management of prostate cancer. Given the similarities between PSA and other KLK gene family members along with limitations of PSA as a biomarker for prostate cancer mainly in reference to diagnostic specificity, the potential roles of other members of this gene family as well as PSA derivatives and isoforms in the management of prostate cancer have been studied extensively. Of these, approaches to measure distinct molecular forms of PSA (free, intact, complexed PSA, and pro-PSA) combined with kallikrein-related peptidase 2 ( KLK2 ), also known as hK2, have been considered holding particular promise in enhancing the diagnosis of prostate cancer. Recently, an integrated approach of applying a panel of four kallikrein markers has been demonstrated to enhance accuracy in predicting the risk of prostate cancer at biopsy. This review presents an overview of kallikreins, starting with the past and current status of PSA, summarizing published data on the evaluations of various KLKs as biomarkers in the diagnosis, prognostication, and monitoring of prostate cancer.